A Descriptive Analysis Of Factors Contributing To Bus Drivers’ Performances While Driving: A Case Study In Malaysia - Siti Nur Atikah, Abdullah; Abdul Adam, Abdullah; Ahmad Rasdan, Ismail; B. M., Deros (Universiti Malaysia Pahang, 2015)
This paper presents the factors contributing to a bus driver’s performance. A bus driver’s performance is important in ensuring the smoothness and safety of a journey. Descriptive survey research design was adopted for the study. The target population was the bus drivers along the east coast of Malaysia (Pahang, Terengganu and Kelantan). The data for the research was collected by using a questionnaire.